2020
DOI: 10.51470/plantarchives.2021.v21.s1.391
|View full text |Cite
|
Sign up to set email alerts
|

Review on Biosynthesis of Silver Nanoparticles and Its Characterization

Abstract: The present review focused the biosynthesis of silver nanoparticles (AgNPs) using plant, bacteria and fungi. Green route of AgNPs could be provided the advantage over the physical and chemical synthesis methods. The conventional methods for the production of NPs were expensive, toxic and non-environment friendly. To overcome these problems, many researchers had been found the precise green route. This review described the methods of green synthesis of silver nanoparticles and their mechanism of antibacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…The data demonstrated that the antimicrobial activity of CH3OH soluble fraction (A1) at all concentrations was highest against E. coli and lowest S. aureus. The results are reported in Table5[20][21][22][23][24][25][26][27][28][29] . Antimicrobial activity of (A1) against bacterial strains.…”
mentioning
confidence: 99%
“…The data demonstrated that the antimicrobial activity of CH3OH soluble fraction (A1) at all concentrations was highest against E. coli and lowest S. aureus. The results are reported in Table5[20][21][22][23][24][25][26][27][28][29] . Antimicrobial activity of (A1) against bacterial strains.…”
mentioning
confidence: 99%